Multiple Intelligences-Based Active Learning in Economics Education: Fostering Student Engagement and Holistic Development - Juanda Prastian Aditia Putra; Shendy Andrie Wijaya; Moh. Usman Kurniawan (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2026)
This study investigates the implementation of Multiple Intelligences-based active learning in Economics education at MA Raudlatus Syabab Sukowono Jember, with a particular focus on the planning, implementation, and evaluation of learning practices in the madrasah context. While previous studies have primarily examined the effectiveness of Multiple Intelligences through quantitative approaches and learning outcomes, this study provides a qualitative understanding of how the approach is translated into classroom planning, instructional practices, and multidimensional assessment in Economics education. A qualitative case study design was employed, involving 15 participants, including an Economics teacher, students, and school administrators. Data were collected through classroom observations, semi-structured interviews, and document analysis. The credibility of the findings was established through triangulation of observations, interviews, and documents, while the data were analyzed using data reduction, data display, interpretation, and conclusion drawing. The findings reveal that the implementation followed three interconnected stages. During the planning stage, teachers designed instructional activities by considering students’ diverse intelligence profiles. During implementation, learning was conducted through discussions, presentations, case analyses, and collaborative activities that encouraged active participation. Evaluation was carried out using multidimensional assessment covering academic achievement, communication, collaboration, participation, and responsibility. These implementation patterns created a more participatory and contextual learning environment while supporting students’ holistic development. The findings provide practical insights into implementing Multiple Intelligences-based active learning in Economics education within madrasahs and contribute to the development of more inclusive and student-centered instructional practices.